2006
DOI: 10.1194/jlr.m500359-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Apo[a] size and PNR explain African American-Caucasian differences in allele-specific apo[a] levels for small but not large apo[a]

Abstract: (16,18,19). In several studies, small apo[a] sizes have been associated with cardiovascular disease (12,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and associations between small apo[a] and cardiovascular disease have remained significant after adjustment for apo [a] level (12, 24-28 Besides the size variation, a C/T polymorphism in the promoter region of the gene (193) and an upstream pentanucleotide repeat (PNR) polymorphism, with 5-12 TTTTA repeats starting at 21,373, have been described in addition to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…1, among African Americans, there was a stepwise increase in Lp[a] levels from e2 to e3 to e4 carriers. Thus, African American e2 carriers had significantly lower levels (17). As seen in Fig.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…1, among African Americans, there was a stepwise increase in Lp[a] levels from e2 to e3 to e4 carriers. Thus, African American e2 carriers had significantly lower levels (17). As seen in Fig.…”
Section: Resultsmentioning
confidence: 51%
“…This study was undertaken to address a possible impact of apoE genotypes on allele-specific apo[a] levels. Previous studies have shown the following: 1) apoE genotypes have a wide impact on plasma lipoprotein levels (21, 38); 2) apoE allele frequency differs between African Americans and Caucasians (22,23,38); 3) plasma Lp[a] levels differ between African Americans and Caucasians (10-14); and 4) the difference in allele-specific apo[a] levels for larger apo [a] size between African Americans and Caucasians is unexplained (17). In our population, we have shown that African Americans have higher allele-specific apo[a] levels compared with Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design has been described (28,29). Briefly, 648 patients, 401 men and 247 women, self-identified as Caucasian (n 5 344), African American (n 5 232), or other (n 5 72) were enrolled.…”
Section: Subjectsmentioning
confidence: 99%